ALTERNATIVE METHOD OF VISCERAL OBESITY ASSESSMENT IN THE DIAGNOSTICS OF METABOLIC SYNDROME - N. G. Veselovskaya; G. A. Chumakova; A. V. Ott; O. V. Gritsenko; N. N. Shenkova (Российский кардиологический журнал)
At present, the existing main and additional criteria of metabolic syndrome (MS) lack a clear justification, which warrants further research.Aim. To assess the potential of waist circumference (WC) and epicardial adipose tissue (EAT) thickness as alternative main criteria of MS.Material and methods. In order to compare the specific features of MS diagnosed by different criteria of visceral obesity (WC and EAT thickness), 186 male patients with general obesity were divided into two groups: MS by the EAT thickness-based criteria and MS diagnosed by the WC-based criteria. In all participants, main and additional metabolic risk factors were assessed. Systolic EAT thickness (mm) was measured at the B-mode echocardiography, in the parasternal long-axis view, behind the free right ventricular wall.Results. In patients with MS by the EAT thickness-based criteria (EAT thickness >7 mm), the levels of insulin (11,2 pIU/ml; 95% confidence interval (CI) 5,219,9 MIU/ml), HOMA-IR index (2,6; 95% CI 1,1-4,6), resistin (12,8 ng/ml; 95% CI 8,1-16,7 ng/ml), and interleukin-6 (12,4 pg/ml; 95% CI 7,6-15,0 pg/ml) were higher than those levels in patients with MS by the WC-based criteria (WC >94 cm):6,9 (3,5-14,2) MIU/ml (p=0,040); 1,8 (0,9-3,4) (p=0,041); 10,8 (6,6-16,1) ng/ml (p=0,044); and 9,8 (4,8-13,6) pg/ml (p=0,044), respectively. Conclusion. Our results have demonstrated that the EAT thickness >7 mm is a more accurate non-invasive marker of insulin resistance and visceral obesity-related neurohumoral and proinflammatory disturbances, compared to the traditional WC criterion (>94 cm in men). In our opinion, the EAT thickness >7 mm could be used as a clarifying criterion of visceral obesity in MS.